Atención al usuario de la Dirección de Registro Civil, identificación y cedulación de la Provincia de Los Ríos Cantón Babahoyo durante el proceso de elecciones en época de pandemia de Covid-19 - Valle Rodríguez, Jimmy David (2021)
The Coordination of the Technical Office of the Civil Registry, Identification and Certification Agency Babahoyo, is a public institution that provides its services in a comprehensive manner through physical and electronic channels with quality, security, efficiency and transparency. It is located on the street by pass and 27 de mayo sector 5 esquinas. On June 25, 2019, the Quality Management System certification under the ISO 9001: 2015 standard was granted by the BUREAU VERITAS Certification House. Its quality policy is committed to providing timely, reliable and close to people services, focused on the efficiency and innovation of its processes and the continuous improvement of its quality management system with competent human talent that meets the needs of users. internal and external at the national and international level (www.registrocivil.gob.ec, sf). It currently has a technology that allows it to offer the services of identification and registration of birth, marriage and death inside and outside its facilities. The information security policy tells us that it is a fundamental asset for the provision of its services and is committed to adopting the best security practices, to guarantee its confidentiality, integrity and availability (www.registrocivil.gob.ec, sf ).